Community Participation in Sports after the Tour de Singkarak Sports Event in Kerinci Regency - Wawan Junresti Daya; Amung Ma'mun; Vanessa Gaffar; Nuryadi Nuryadi (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2023)
Tour de Singkarak (TdS) is an international cycling event held by the West Sumatra government since 2009. The problem of this study was that the significance of the effect or impact of the Tour de Singakarak (TdS) in increasing the participation rate of people in sports in Kerinci Regency was not yet known. The authors used a quantitative method to reveal research findings in this study. The cross-sectional design was used to collect data. Participants of this study were 509 people spread over 18 sub-districts in Kerinci Regency. The data were analyzed using SPSS software. The results showed that the Tour de Singkarak (TdS) bicycle racing event increased the community sports participation rate in Kerinci Regency by 65%. It indicates that the Tour de Singakrak (TdS) bicycle racing event effectively increases community sports participation rates, especially in Kerinci Regency. Therefore, future sporting events must be carried out continuously to maintain community participation in sports. The high participation of people in sports in an area will bring many benefits to that area.